Research priorities for the development of appropriate feeding systems for dairy production in sub-Saharan Africa - Olaloku, E.A.; Debrah, S.K. (International Livestock Centre for Africa, 1992)
Inadequate feed supplies remain a major constraint to sustainable cattle production in general, and milk production in particular, in smallholder production systems throughout sub-Saharan Africa. In the emerging peri-urban dairy production systems in West and central Africa, for example, poor development of feed resources has invariably resulted in milk production being sustained at comparatively high feed costs, thus reducing the competitiveness of locally produced milk. Given the opportunities for generating increased quantities of crop residues from many of the crop production projects assisted by international agencies (e.g., World Bank, Global 2000), there is an urgent need to identify research priorities in the development of feeding systems appropriate to the different smallholder production systems. Such feeding systems will have to incorporate a new approach to cattle management, involving cultivation of specialised fodder crops and harvesting and conservation of crop residues for milk production.